Small RNA responses of Culex mosquitoes and cell lines during acute and persistent virus infection. (June 2019) - Rückert, Claudia; Prasad, Abhishek N.; Garcia-Luna, Selene M.; Robison, Alexis; Grubaugh, Nathan D.; Weger-Lucarelli, James; Ebel, Gregory D.
Abstract: RNA interference is a crucial antiviral mechanism in arthropods, including in mosquito vectors of arthropod-borne viruses (arboviruses). Although the exogenous small interfering RNA (siRNA) pathway constitutes an efficient antiviral response in mosquitoes, virus-derived P-element induced wimpy testis (PIWI)-interacting RNAs (piRNAs) have been implicated in the response to alpha-, bunya- and flaviviruses in Aedes spp. mosquitoes. Culex mosquitoes transmit several medically important viruses including West Nile virus (WNV), but are considerably less well studied than Aedes mosquitoes and little is known about antiviral RNA interference in Culex mosquitoes. Therefore, we sequenced small RNA (sRNA) libraries from different Culex cell lines and tissues infected with WNV. The clear majority of virus-derived sRNA reads were 21 nt siRNAs in all cell lines and tissues tested, with no evidence for a role of WNV-derived piRNAs. Additionally, we aligned sRNA reads from Culex quinquefasciatus Hsu cells to the insect-specific rhabdovirus, Merida virus, which persistently replicates in these cells. We found that a significant proportion of the sRNA response to Merida virus consisted of piRNAs. Since viral DNA forms have been implicated in siRNA and piRNA responses of Aedes spp. mosquitoes, we also tested for viral DNA forms in WNV infected Culex cells. We detected viral DNA in Culex tarsalis cells infected with WNV and, to a lesser amount, WNV and Merida virus-derived DNA in Culex quinquefasciatus Hsu cells. In conclusion, Hsu cells generated Merida virus-derived piRNAs, but our data suggests that the major sRNA response of Culex cells and mosquitoes to WNV infection is the exogenous siRNA response. It is also evident that sRNA responses differ significantly between specific virus-mosquito combinations. Future work using additional Culex- borne viruses may further elucidate how virus-derived piRNAs are generated in Culex cells and what role they may play in controlling replication of different viruses. Graphical abstract: Image 1 Highlights: Culex mosquitoes and cell lines produce mainly 21 nt virus-derived small RNAs upon West Nile virus infection. PIWI genes are differentially expressed in Culex quinquefasciatus midguts and ovaries. Culex quinquefasciatus Hsu cells produce piRNAs derived from the insect-specific rhabdovirus, Merida virus. Viral DNA forms were generated in Culex tarsalis cells, but only few viral DNA forms were found in Culex quinquefasciatus cells.